The Brain-Gut-Microbiota Axis in Depression: Medical Progress - Siejka , Agata; Wanat, Joanna; Homa, Wojciech; Dzikowska, Izabela; Stefaniak, Daria; Zielińska, Weronika; Chról, Michał; Warunek, Aleksandra; Gronowicz, Gabriela (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: In recent years, more and more scientific research has paid attention to determining the role of gut microbiota in maintaining the body’s homeostasis. It is attributed not only to the functions related to digestion but also to many others that may seem unrelated to the digestive tract. This includes, among others, creating immunity and psyche, through a strong influence on the gut-brain axis. The gut microbiota colonizes the digestive tract already in the first days after birth. Over time it undergoes significant changes, both quantitative and qualitative. This affects the ability to perform the functions mentioned above. This study aims to review current scientific research on the gut microbiota and the gut-brain axis and to determine how they may participate in the pathogenesis of depressive disorders. Brief Description of the State of Knowledge: Changes in the number and proportion of microorganisms that create the gut microbiota are associated with severe disorders. Disturbances in the gut-brain axis can affect many processes, which are the basis of neurological and psychiatric conditions. Due to the prevalence and limitations of currently used methods of treating depressive disorders, scientists emphasize the necessity of perceiving this disease as one of the symptoms of a disturbed gut-brain axis. Understanding the entire pathophysiology could help in defining strict procedures for the treatment of the aforementioned dysbiosis. Summary: Depression affects a significant group of patients in everyday medical practice. Even for experienced doctors, it is a major diagnostic and therapeutic challenge. Diagnosis, treatment, and prevention of gut dysbiosis may prove to be an effective support for classic depression therapy.